A methods engineering study on BAT's Bag and Wallet Industry - Dompor, Lorena; Lynn, Jaimini Juris; Marquez, Diana (Diliman, Quezon City College of Engineering, 2000)
BAT's Bag and Wallet Industry is a sub-contractor of Allegro Pacific Philippines, exporter of bags and wallets. It manufactures 12 product line using 24 workers and 22 machines, in varying numbers. A visit to the its plant and interviews with its management and people revealed that the major issue is production delay. To validate this concern, the group decided to conduct a study on one product-the 100CS2A. Techniques used were time study, operations process chart and multiple activity chart. Major data that supported the analysis of the situation included, among others: a. Workers A, E, F, G, I, J & K, who use the sewing machines are paid by piece. Workers B, C, D & H are on daily rate, with Worker B acting as Supervisor; b. There is a lot of idle time because workers are allowed to start anytime they want. c. Sewing machines are more than enough for the product line. These data and analysis of the situation revealed that the production of the required 1000 pieces 100CS2A can be done in 2.7 days-way below the required four days. However, each worker should not work later than the schedule below: Worker A, B, C, E Day 2 10 am; Worker F, G, H, I, J Day 2 1pm, Worker K Day 2 4 pm. Worker B will still act as Supervisor, but Worker D need not work with the team since Worker C can finish the job without delaying the whole process.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: BAT's Bag and Wallet; Luggage industry; Systems analysis